PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, KEPEMILIKAN MANAJERIAL, DAN GENDER DIVERSITY TERHADAP MANAJEMEN LABA - Nur Wakidatur Rohmah; Dianita Meirini (Politeknik Negeri Ambon, 2022)
This research aims to determine the effect of firm size, profitability, managerial ownership, and gender diversity on earnings management. The population in this research were companies listed on the LQ45 index on the Indonesia Stock Exchange for the period 2016 to 2020. The research sample was selected using a purposive sampling method with a total of 24 companies and a period of 5 years. The research uses quantitative methods with panel data regression methods. The results showed that firm size had no significant effect on earnings management, profitability had a significant positive effect on earnings management, managerial ownership had no significant effect on earnings management, and gender diversity had no significant effect on earnings management.